ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI PADA USAHATANI PADI SAWAH DI DESA POSONA KECAMATAN KASIMBAR KABUPATEN PARIGI MOUTONG - Rahmat, Rahmat; Alam, Max Nur; Kalaba, Yulianti (AGROTEKBIS, 2017)
This research aims to determine the efficiency of use of inputs of land, seed, fertilizer, labor, and pesticides on the farm production of paddy in Posona village, Kasimbar District, Parigi Moutong Regency. This research was conducted in December 2015.The data used in this study derived from primary and secondary data. The number of respondents used as many as 34 farmers were selected using simple random sampling technique.The analysis used is the Cobb Douglas production function analysis.The results showed that simultaneous independent variable (Xi) has significant effect on the dependent variable (Y) except the variable oflabor (X4), and pesticides (X5). Aspartial, land area (X1), seeds (X2), and fertilizers (X3), significantly affect the production of paddy in the Village Posona, Kasimbar District Parigi Moutong Regency, with the value of sig 0.000 <0.05 in Î± 5%. Analysis of efficiency showsed that the total value (k) of the variable land area (X1), seeds (X2), fertilizers (X3) labor (X4) and pesticides (X5), was greater than 1, it mean that all production inputs used in farming rice paddy in the village of Posona,in terms of the price of each input is expressed not efficient production except labor variable (X4) and Pesticides (X3) having a value of 0:01 and 0 which is smaller than 1 so inefficient.Â Key Words :Efficiency, Farming, Input, and Paddy.